Professional business connectivity services in SharePoint 2010 - Hillier, Scot; Stevenson, Brad (Indianapolis, Indiana : Wiley Publishing Incorporation, 2011)
A guide to BCS discusses its relationship to other components of SharePoint, its role in the business environment, how to create custom solutions using server-side and client-side object models, and its security solutions.
Keywords: Microsoft SharePoint (Electronic resource)